Ibn al-Azraq's political thought: a study of Bada'i' al-silk fi taba'i' al-mulk - Isahak , Aldila (VDM Verlag Dr. Muller, 2010)
Finding a Muslim polity through leadership based on iman that is rooted in taqwa Ibn al-Azraq says is the answer to the best governance. An Islamic leadership in this form, he says will prevent the extinction of any Muslim polity. This prevention is possible because, he says, a leader, who is conscious of the trust given by Allah to administer a state, would receive not only the blessings of Allah but also win over the hearts of his people. Ibn al-Azraq’s political thought is discerned through a comparative analysis of the two editions of Bada’i al-silk fi taba’i al-mulk, where the influence of Ibn Khaldun on Ibn al-Azraq’s political thought is clearly revealed. The survey of socio-political milieu in which Ibn al-Azraq lived illustrates how the conflicts of the Muslim leadership of Granada persisted despite its war with the Christians. In this context and in formulating his political thought, Ibn al-Azraq combined usul al-fiqh and syllogism as his methodology. This methodology has led him to synthesise Ibn Khaldun’s theory on ‘asabiyyah as the catalyst for the rise and fall of a civilization, and the shari‘ah. This formulates the premises where the rational justification and the religious justification for the necessity of leadership are combined, whereas previous scholars have failed to assign Ibn Khaldun’s theory on ‘asabiyyah as the rational justification for the necessity of leadership. This is clarified in the review of Bada'i al-silk fi taba’i al-Mulk. In his discussion on Muslim polity, Ibn al-Azraq presented various qualifications and recommendations related to political ethics which the leader of the state should possess. Ibn al-Azraq also elaborates on the two principles of governance, namely, justice and consultation in addition to state various institutions which he thinks must be established as part of governance. The study of Ibn al-Azraq’s political thought in his book Bada'i al-silk fi taba'i al-mulk reveals the significant contribution in the ingenuity of ascribing Ibn Khaldun’s theory of ‘asabiyyah as the rational justification to the necessity of leadership in human societies, while agreeing with other scholars on shari‘ah as the religious rationale.